Incidental Brain Magnetic Resonance Imaging Findings and the Cognitive and Motor Performance in the Elderly: The Shanghai Changfeng Study - Wang, Liangqi; Lin, Huandong; Peng, Yifeng; Zhao, Zehua; Chen, Lingyan; Wu, Li; Liu, Ting; Li, Jing; Liu, Anna; Lo, Chun-Yi Zac; Gao, Xin (Frontiers in Neuroscience, 2021)
Background: The incidental findings (IFs) from imaging observations are increasing frequently discovered. The IFs show the potential clues of structural abnormalities underlying cognitive decline in elders. Detecting brain IFs and their relationship with cognitive and behavioral functions is helpful to providing the information for clinical strategies. Methods: Five hundred and seventy-nine participants were recruited in the Shanghai Changfeng Study. All participants performed the demographic, biochemical, cognitive functions and gait speed assessment; and underwent the high-resolution multimodal magnetic resonance imaging scans. We calculated the detection rate of brain IFs. The association between cardiovascular risk factors and IFs, the associations between IFs and cognitive and motor functions were assessed using regression models. The relationships between gray matter volume (GMV) and cognitive function, and gait speed were assessed with/without adjusting the IFs to evaluate the effects of potential IFs confounders. Results: IFs were found in total 578 subjects with the detection rate of 99.8%. Age and blood pressure were the most significant cardiovascular risk factor correlated with IFs. IFs were found to be negatively associated with MoCA, MMSE and gait speed. The GMV was found to be positively correlated with the cognitive function without adjusting the white matter hyperintensity, but not if adjusted. Conclusions: IFs are commonly found in the elderly population and related to brain functions. Adequate intervention of IFs related cardiovascular risk factors may prevent the brain function decline. We also suggest that IFs should be considered as confounding factors that may affect cognitive issues on the structural neuroimaging researches in aging or diseases.